Designing Packed Palm Cooking Oil Distribution at Traditional Market in Jakarta Using Fuzzy Clustering - Teja Primawati Utami; Syamsul Ma’arif; Yandra Arkeman; Liesbetini Hartoto (Balai Besar Penelitian dan Pengembangan Pascapanen Pertanian, 2015)
Referring to the Indonesian National Standard number 7709 year 2012 that palm cooking oil should be fortified with vitamin A, so that the distribution process required packaging to protect Vitamin A. Besides packaging palm cooking oil can make the content hygiene. Packaged cooking oil was distributed from the factory to the traditional market directly. In accordance with Regulation of the Minister of Industry of the Republic of Indonesia Number 87 year 2013 on the application of ISO palm olein is mandatory and Trade Minister Regulation number 80 year 2013 on compulsory packaging cooking oil, so need a mechanism to bulk cooking oil distribution.Simple packaging in the traditional market of producers to effective and efficient consumer. The purpose of this paper is to design a system of distribution of cooking oil from producers to consumers in traditional markets by creating a central cluster calls distribution center. Design models created using fuzzy clustering method. The results of this study create 15 clusters of traditional markets in Jakarta.Merujuk pada Standar Nasional Indonesia nomor 7709 tahun 2012 bahwa minyak goreng sawit perlu ditambahkan vitamin A, sehingga dalam proses distribusinya diperlukan pengemasan untuk melindungi Vitamin A tersebut. Tujuan pengemasan minyak goreng curah ke kemasan sederhana juga dilakukan untuk menjaga higienitas dan melindungi konsumen dari praktek pengoplosan. Sesuai dengan Peraturan Menteri Perindustrian Republik Indonesia nomor 87 tahun 2013 tentang pemberlakuan SNI minyak goreng sawit secara wajib dan Peraturan Menteri Perdagangan nomor 80 tahun 2013 tentang minyak goreng wajib kemasan, maka diperlukan suatu mekanis pendisribusian minyak goreng curah ke kemasan sederhana di pasar tradisional dari produsen ke konsumen yang efektif dan efisien. Tujuan dari makalah ini adalah mendesain sistem distribusi minyak goreng dari produsen ke konsumen di pasar tradisional dengan cara membuat klaster yang otomatis ditentukan sentral distribusinya. Desain model dibuat dengan menggunakan metode Fuzzy clustering. Hasil dari penelitian ini adalah terdapat 15 klaster pasar tradisional di Jakarta dengan masing-masing satu sentra distribusi.